Sobre o limiar para a produção de pares e localização de partículas sem spin - Cardoso, Tatiana R. [UNESP]; de Castro, Antonio S. [UNESP] (My University, 2007)
The one-dimensional Klein-Gordon equation is investigated with the most general Lorentz structure for the external potentials. The analysis of the scattering of particles in a step potential with an arbitrary mixing of vector and scalar couplings reveals that the scalar coupling contributes for increasing the threshold energy for the particle-antiparticle pair production. Furthermore, it is shown that the pair production is only feasible whether the vector coupling exceeds the scalar one. An apparent paradox concerning the localization of a particle in an arbitrarily small region of space, due to the presence of the scalar coupling, is solved by introducing the concept of effective Compton wavelength. Copyright by the Sociedade Brasileira de Física.
On the threshold for the pair production and localization of spinless particles
Keywords: Compton wavelength; Klein's paradox; Klein-Gordon equation; Localization; Pair production